Coping with Threats, Losses, and Challenges - Bjorck, Jeffrey P.; Cohen, Lawrence H. (Journal of social and clinical psychology, 1993)
Subjects predicted more use of Problem Solving, and less use of Religious Coping and Wishful Thinking, when confronted with Challenges compared to Threats and Losses. For Threats compared to Losses, subjects planned to use more Problem Solving and Religious Coping, and less Emotional Social Support. (Original abstract-amended)